Putusan Ultra Petita Penanganan Kasus Korupsi Menurut Perspektif Hakim - Pudyatmoko, Y.Sri; Aryadi, G. (UI Scholars Hub, 2023)
This research aims to obtain an overview of ultra petita decisions in corruption cases from a law enforcement perspective. The method used in this research is a normative legal research method, using a case approach. The research was conducted by analyzing the views of several judges regarding ultra petita decisions in corruption cases. The research results show that judges in handling corruption cases refer to regulations from the Supreme Court. In accordance with these guidelines, judges use comprehensive considerations in making decisions. According to the judge in the ultra petita decision against a convict in a corruption case, something like this could have happened because of the public prosecutor's error in making charges. Some judges are of the view that when deciding cases, including corruption cases, the judge must consider all the facts in the trial as well as various things that give the judge confidence. Judges view that they are not bound by the prosecutor's demands alone, but rather by the indictment, the facts of the trial, truth and justice.